Influence of the training: " Clinical practice based on the evidence " in the daily practice of the nurse - Ligia Rojas Valenciano; Allan Rodríguez Artavia; Manuel Monge Blanco (Universidad de Costa Rica, 2013)
The aim of this article is to present the results of the project Not. 421-B1-261: Influence of the training of the Clinical Practice Based on the Evidence on the daily practice of the professional of nursing, approved by the Vicerrectoría of Investigation of the University of Costa Rica. The commitment to renew the practice of Nursing in Costa Rica relates in a direct way to the improvement of the health of the society both in the collective thing and in the individual thing, in order to reduce the mistakes in the practice. A search was realized in EBSCO's databases, PubMed, Academic Research Completes, MedLine Plus and Scielo. A preliminary search was carried out, then limits of search interfered per date and describers; finally, for the critical analysis they were included only to complete text by title and they summarize 30 documents that included reviews of literature, primary studies and conceptual frames that were relevant to give response to the clinical question. Of 30 documents only it was considered six of them by your content, methodological structure and quality. Though there was not situated a forceful and direct response to the clinical question raised in this study, for the effected review it is possible to conclude that the professionals of Nursing consider to be essential the enrichment of a clinical practice based on the evidence, which generates a major quality and safety in the executed care.